Electrospun Zn-doped Ga2O3 nanofibers and their application in photodegrading rhodamine B dye. Issue 4 (15th February 2021) - Du, Fenqi; Yang, Dongmei; Sun, Yue; Jiao, Yang; Teng, Feng; Fan, Haibo
Abstract: Ultrawide band gap semiconductor materials have attracted considerable attention in recent years owing to their great potential in the photocatalytic field. In this study, Zn-doped Ga2 O3 nanofibers with various concentrations were synthesized via electrospinning; they exhibited a superior photocatalytic degradation performance of rhodamine B dye compared to that of undoped Ga2 O3 nanofibers. The Zn dopant replaced Ga sites via replacement doping, which could increase the concentration of oxygen vacancies and lead to enhanced photocatalytic properties. When the Zn concentration increased, a Ga2 O3 /ZnGa2 O4 hybrid structure formed, which could further enhance the photocatalytic performance. The separation of photogenerated carriers due to Zn doping and heterojunctions were the primary causes of the enhanced photocatalytic performance. This study provides experimental data for the fabrication of high-performance photocatalysts based on Ga2 O3 nanomaterials.